Study of the structure, electrical properties, and energy storage performance of ZnO-modified Ba0.65Sr0.245Bi0.07TiO3 Pb-free ceramics. Issue 1 (January 2020) - Li, Yang; Zhang, Ling; Yu, Linjiang; Li, Dequan; Meng, Haoyan; Ai, Qiao; Hu, Jinzhu; Jin, Li; Gao, Jinghui; Liu, Gang
Abstract: Barium titanate ceramic is frequently used as a ferroelectric material and can be applied in the pulse power field in energy storage devices. Its properties, including dielectric, ferroelectric, and energy storage properties, can be significantly improved through doping. In this work, we prepared a series of (1- x )Ba0.65 Sr0.245 Bi0.07 TiO3 - x ZnO ( x = 0.005, 0.01, 0.02, 0.03) lead-free bulk relaxor ferroelectric ceramics by a traditional die-pressing processing route. The uniformity of the grain sizes for these ceramics was improved, and the grains were refined when a certain amount of ZnO was introduced into BaTiO3 -based ceramics. In addition, the breakdown strength was improved in the case where the relaxor behavior was not significantly improved. It should be noted that the sample doped with 0.02 mol Zn showed the maximum room-temperature storage density (1.51 J/cm 3 ) at the largest electric field strength (210 kV/cm). At the same time, this ceramic exhibited good stability to temperature (60–150 °C) and frequency (10–100 Hz) variations, as well as fantastic fatigue resistance (10, 000 charge-discharge cycles). This paper presents in-depth studies of the structure, morphology, electrical properties, and energy storage performance of ZnO-modified BaTiO3 -based ceramics.